2018
DOI: 10.1111/jgs.15452
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Model to Improve Hospital Care of Older Adults with Cognitive Impairment: A Propensity Score–Matched Analysis

Abstract: A multicomponent intervention of geographic cohorting, multidisciplinary approach, PES, and staff education may offer a new paradigm in the management of hospitalized older adults with cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…These findings and conclusions are in line with other studies on hospital care that suggest that an increased staff ratio or the implementation of multiple components, which particularly address the needs of patients with dementia, leads to reduced use of physical restraints and psychotropic drug use and improves the quality of care 57 58. Furthermore, dementia-specific educational programmes, as implemented in the special care ward, have positive effects on nurses with regard to their interaction with patients with dementia.…”
Section: Discussionsupporting
confidence: 86%
“…These findings and conclusions are in line with other studies on hospital care that suggest that an increased staff ratio or the implementation of multiple components, which particularly address the needs of patients with dementia, leads to reduced use of physical restraints and psychotropic drug use and improves the quality of care 57 58. Furthermore, dementia-specific educational programmes, as implemented in the special care ward, have positive effects on nurses with regard to their interaction with patients with dementia.…”
Section: Discussionsupporting
confidence: 86%
“…The studies exploring family caregivers' satisfaction with care in special geriatric units revealed both less dissatisfaction [47] and more satisfaction with care [40] compared to standard care wards. Additionally, evaluation of special geriatric unit models revealed lower in-hospital mortality, shorter stays, less need for constant or enhanced observations, reduced use of psychotropic medication and occurrence of delirium compared to standard wards [42,46]. Evaluation of the effectiveness of an acute hospital dementia unit adopting a person-centred care protocol moderating intrusive interventions revealed positive impacts on quality of life such as decreased agitation in people with dementia and confirmed cost-effectiveness [50].…”
Section: Interventionsmentioning
confidence: 83%
“…has distinguishable features and a view of the outdoors, and 2) staff's experience of the physical environment as a barrier for patient safety. Experiences and needs of patients with dementia related to the physical environment in acute hospital wards were described from the perspective of staff [25,29,[33][34][35][36] persons with dementia [28,34,46], family carers [34] and by observations [31,35]. The studies demonstrate the importance of an environment that enables independence for people with cognitive impairment by making it easier to navigate the surroundings.…”
Section: Categories Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…• Environmental changes (Sinvani et al, 2018) Retrospective chart review. "Sitter" "Constant observation" "companions" "one-to-one patient care" "the "Special" role" • Untrained role "Communication"…”
Section: "Specialling"mentioning
confidence: 99%